The small mammals of the Middle/Later Stone Age the site of Goda Buticha (Eastern Hararghe, Ethiopia): contribution to the knowledge of the Upper Pleistocene - Holocene transition in East Africa - (:unkn) unknown (My University, 2014)
The study of the small mammals from the late Pleistocene/Holocene site of Goda Buticha (Dire Dawa, Ethiopia), through the use of different methods, allowed us to better understand the small mammal diversity as well as paleoecological changes has in East Africa, and more specifically in Ethiopia, during the upper Pleistocene - Holocene transition. The taphonomic analysis also provided information on the origin of the small mammal accumulations. No water dispersal of bones occurred in the cave, and the faunal remains (especially Murids and Gerbils) were accumulated by opportunistic predators such as Barn Owl (Tyto alba), Spotted Eagle owl (Bubo africanus) or Giant Eagle Owl (Bubo lacteus). The paleoecological study highlights landscape and climate changes throughout time, with a transition from open/arid habitats (upper Pleistocene levels) to wetter and wooded habitats (Holocene levels). This work highlights the importance of studying small mammals as a usefull tool for palaeoenvironmental and biogeographical studies in relation to human occupations in East Africa at the end of the upper Pleistocene (in and out of Africa dispersal of Homo sapiens) and at the beginning of the Holocene (« Back to Africa »).
Keywords: African Research